Nanodispersions of Polyelectrolytes Based on Humic Substances: Isolation, Physico-Chemical Characterization and Evaluation of Biological Activity - Elena V. Uspenskaya; Anton V. Syroeshkin; Tatiana V. Pleteneva; Ilaha V. Kazimova; Tatiana V. Grebennikova; Irina T. Fedyakina; Varvara V. Lebedeva; Oleg E. Latyshev; Olesia V. Eliseeva; Viktor F. Larichev; Timur M. Garaev; Tatiana V. Maximova; et al. (MDPI AG, 2021)
Natural polyelectrolytes, including in the form of complexes with colloidal particles, are increasingly used in pharmacy due to the possibility of regulated attachment of medicinal substances and their targeted delivery to the target organ. However, the formation, stability, and molecular-mass characteristics of polyelectrolyte nanodispersions (ND) vary depending on the nature and composition of the medium of their origin. This is due to the lack of standardized approaches to quality control and regulatory documentation for most natural ND. In this paper, we first introduced the isolation, followed by investigations into their physico-chemical properties and bioactivity. Using the dried droplet method, we were able to detect the "coffee ring effect". Fractographic studies of the surface structure of EHA and FA dried samples using SEM showed its heterogeneity and the presence of submicron particles encapsulated in the internal molecular cavities of polyelectrolyte. FTIR spectroscopy revealed the ND chemical structure of benzo-α-pyron and benzo-γ-pyron, consisting of nanoparticles and a branched frame part. The main elements detected by X-ray fluorescence in humic substance extract and fulvic acid include Si, P, S, K, Ca, Mn, Fe, Cu, Zn, whereas Fe is in high concentrations. The UV-spectra and fluorescent radiation demonstrated the possibility of studying the effect of the fulvate chromone structure on its optical properties. It is shown that dilution of the initial solutions of polyelectrolytes 1:10 contributes to the detection of smaller nanoparticles and an increase in the absolute value of the negative ζ-potential as a factor of ND stability. A study of the EHS effect on the SARS-CoV-2 virus infectious titer in the Vero E6 cell showed the effective against virus both in the virucidal scheme (the SI is 11.90-22.43) and treatment/prevention scheme (the SI is 34.85-57.33). We assume that polyelectrolyte ND prevent the binding of the coronavirus spike glycoprotein to the receptor. Taking into account the results obtained, we expect that the developed approach can become unified for the standardization of the ND natural polyelectrolytes complex, which has great prospects for use in pharmacy and medicine as a drug with antiviral activity.